Urbanisation in the Island Pacific : towards sustainable development - Connell, John, 1946- (Routledge Pacific Rim geographies, 2002)
Managing rapid urban growth presents a significant challenge in the small independent countries of the Pacific Islands. Although they originated in colonial times, the towns and cities are now distinctively post-colonial, with economies, environments and social structures that reflect unique island characteristics. This transformation has stimulated new concerns, such as the causes and effects of pollution, the need for employment for landless migrants, the need for adequate and affordable housing and the financing of expanding urban services. This book explores the diversity of the urban exper.